Short-arc discharge lamp

CN115547807BActive Publication Date: 2026-10-09USHIO INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210402427.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-06-30
Filing Date
2022-04-15
Publication Date
2026-10-09
Estimated Expiration
2042-04-15

AI Technical Summary

Technical Problem

然而,即便在阳极的表面设置有凹凸,根据形成于其之上的散热层的厚度,也有时在散热层的表面不形成凹凸(反映了阳极表面的凹凸形状的凹凸),无法有效地散热

Benefits of technology

[0029] Based on these structures, the heat dissipation of the electrodes can be further improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115547807B_ABST
    Figure CN115547807B_ABST
Patent Text Reader

Abstract

Provided is a short-arc discharge lamp having excellent heat dissipation, a long service life, and suppressed evaporation of the electrode material when the lamp is lit. The short-arc discharge lamp includes a light-emitting tube and a pair of electrodes disposed opposite each other inside the light-emitting tube. At least one of the electrodes has a cylindrical outer peripheral surface that includes a concave-convex structure having a plurality of circumferential grooves extending in the circumferential direction arranged in the axial direction, and a first coating film containing ceramic formed on the concave-convex surface of the concave-convex structure. When the groove depth of the circumferential grooves is a (μm) and the distance from the groove bottom of the circumferential grooves to the surface of the first coating film is b (μm), the relationship 1 ≤ b / a ≤ 4 is satisfied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a short-arc discharge lamp. Background Technology

[0002] Short-arc discharge lamps (hereinafter also referred to as "lamps") are widely used as light sources in exposure apparatuses for the manufacturing processes of semiconductor components or liquid crystal display components. These short-arc discharge lamps are constructed by arranging the anode and cathode opposite each other within a light-emitting tube, and by sealing the tube with luminescent materials such as mercury or xenon.

[0003] In such short-arc discharge lamps, it is known that the heat load applied to the anode is high during illumination, leading to evaporation of the electrode material due to anode overheating. This evaporated material adheres to the inner wall of the light-emitting tube, causing the tube to blacken. When the light-emitting tube blackens, its light transmittance decreases.

[0004] To solve this problem, there is a known technique of forming a heat dissipation layer on the electrode surface to suppress the temperature rise of the electrode. In the following Patent Document 1, a lamp is disclosed in which a heat dissipation layer containing an oxide of at least one metal is formed on the outer surface of the anode.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 2004-259639

[0008] The problem that the invention aims to solve

[0009] In the lamp described in Patent Document 1, in order to improve the adhesion strength of the heat dissipation layer, an uneven surface with an Rmax of 10 μm or more is formed on the surface of the anode, and a heat dissipation layer is provided on its surface. Moreover, examples are disclosed in which the surface layer of the heat dissipation layer is set to an Rmax of 2 μm to 100 μm.

[0010] To improve heat dissipation, the surface of the heat dissipation layer is ideally designed to be uneven. However, even if the surface of the anode is uneven, depending on the thickness of the heat dissipation layer formed on it, sometimes the surface of the heat dissipation layer may not have unevenness (reflecting the uneven shape of the anode surface), thus failing to dissipate heat effectively. Summary of the Invention

[0011] The present invention was made in view of the above-mentioned problems, and its object is to provide a long-life short-arc discharge lamp with excellent heat dissipation and suppressed evaporation of electrode material when the lamp is lit.

[0012] Solution for solving the problem

[0013] The short-arc discharge lamp of the present invention includes a light-emitting tube and a pair of electrodes disposed opposite to each other inside the light-emitting tube.

[0014] At least one of the electrodes in the pair has a cylindrical outer peripheral surface.

[0015] The outer peripheral surface has: an uneven structure with a plurality of circumferential grooves arranged axially and extending circumferentially; and a first coating comprising ceramic formed on the uneven surface of the uneven structure.

[0016] When the groove depth of the circumferential groove is set to a (μm) and the distance from the bottom of the circumferential groove to the surface of the first coating is set to b (μm), the following relationship (1) is satisfied.

[0017] 1≤b / a≤4 (1)

[0018] According to this structure, the surface of the first coating has an uneven shape reflecting the uneven structure, thus improving heat dissipation. As a result, the electrodes of the short-arc discharge lamp of the present invention have excellent heat dissipation, so the evaporation of the electrode material when the lamp is lit is suppressed, and the lifespan is extended.

[0019] In the short-arc discharge lamp of the present invention, the ceramic may also have a structure comprising at least one of metal oxides, metal carbides, metal borides, metal silicides, and metal nitrides.

[0020] Alternatively, in the short-arc discharge lamp of the present invention, the ceramic may also have a structure in which zirconium oxide is the main component.

[0021] Furthermore, in this specification, "main ingredient" is used as a term that means the ingredient with the highest content under quality standards.

[0022] Based on these structures, the first coating can function as a high-emissivity film with excellent emissivity.

[0023] In the short-arc discharge lamp of the present invention, the structure can also be as follows:

[0024] The electrode has an electrode front portion whose outer diameter decreases as it faces the front end.

[0025] A second coating is formed on the surface of the front portion of the electrode, the second coating comprising a metal with a higher melting point than the ceramic.

[0026] Alternatively, the short-arc discharge lamp of the present invention may also have the following structure:

[0027] The electrode has an electrode front portion whose outer diameter decreases as it faces the front end.

[0028] Microgrooves are formed on the surface of the front part of the electrode.

[0029] Based on these structures, the heat dissipation of the electrodes can be further improved. Attached Figure Description

[0030] Figure 1 This is an explanatory diagram showing the structure of the short-arc discharge lamp of this embodiment.

[0031] Figure 2 yes Figure 1 An enlarged view of region II of the short arc discharge lamp shown.

[0032] Figure 3 yes Figure 2 An enlarged cross-sectional view of region III shown.

[0033] Figure 4 This is an enlarged cross-sectional view of the case where the thickness of the first coating is thick.

[0034] Figure 5 It is an SEM image depicting a cross-section of the anode.

[0035] Figure 6 It is an SEM image depicting a cross-section of the anode.

[0036] Figure 7 This is a front view of the anode in other embodiments.

[0037] Figure 8 This is a front view of the anode in other embodiments. Detailed Implementation

[0038] The embodiments of the short-arc discharge lamp of the present invention will be described with reference to the accompanying drawings. Furthermore, the following drawings are schematic diagrams, and the dimension ratios shown in the drawings may not necessarily correspond to the actual dimension ratios, nor may they necessarily be consistent between the different drawings.

[0039] The following explanation will be provided with appropriate reference to the XYZ coordinate system. Furthermore, in this specification, when expressing direction, if a positive or negative orientation is distinguished, it will be indicated by adding a positive or negative sign, such as "+X direction" or "-X direction". If a direction is expressed without distinguishing positive or negative, it will be abbreviated as "X direction". That is, in this specification, the abbreviation "X direction" includes both "+X direction" and "-X direction". The same applies to the Y and Z directions.

[0040] Figure 1This is an explanatory diagram showing the structure of the short-arc discharge lamp according to this embodiment. The short-arc discharge lamp 1 (hereinafter referred to as "lamp 1") includes a light-emitting tube 2 and an anode 3 and a cathode 4 disposed opposite to each other inside the light-emitting tube 2. The anode 3 and the cathode 4 are each supported by a conductor rod 5.

[0041] The lamp 1 in this embodiment is a large lamp used in the exposure apparatus used in the manufacturing process of semiconductor devices or liquid crystal display devices, for example, with a rated power of 2kW to 35kW.

[0042] Light-emitting tube 2 is formed by expanding the center of a glass tube. Light-emitting tube 2 is the region of the glass tube whose inner diameter increases as it extends from both ends toward the center in the X direction. The shape of light-emitting tube 2 is spherical or ellipsoidal.

[0043] The light-emitting tube 2 has a pair of sealing tube portions 21 extending continuously from both ends of the light-emitting tube 2 in opposite directions along the X direction. The light-emitting tube 2 and the sealing tube portions 21 are integrally formed together, for example, from quartz glass. The central axes of each of the pair of sealing tube portions 21 overlap each other. Figure 1 The axis X1 is represented.

[0044] A light-emitting space S1 is formed inside the light-emitting tube 2. A light-emitting substance such as mercury is sealed in the light-emitting space S1.

[0045] Inside the light-emitting tube 2, the anode 3 and the cathode 4 are arranged opposite to each other in the X direction. In this embodiment, the short-arc discharge lamp refers to a discharge lamp in which the anode 3 and the cathode 4 are arranged opposite to each other with a gap of less than 40 mm (the value at room temperature without thermal expansion). In this embodiment, the anode 3 is made of tungsten, and the cathode 4 is made of thorium-plated tungsten.

[0046] The guide rod 5 is connected to the anode 3 and the cathode 4, and extends in the X direction within the sealed tube portion 21. The anode 3 and the cathode 4 are fixed to the front end of the guide rod 5. The central axis of the guide rod 5 can overlap with the axis X1. The guide rod 5 is made of a material containing a high-melting-point metal such as tungsten.

[0047] The lamp holder 8 covers the side of the sealed tube 21 that is away from the anode 3 and the cathode 4. The lamp holder 8 is electrically connected to the conductor rod 5.

[0048] Figure 2 yes Figure 1 An enlarged view of region II of lamp 1 is shown. A first coating 6 containing ceramic is formed on a portion of the surface of anode 3.

[0049] The anode 3 has a cylindrical body portion 3a centered on axis X1 and an electrode front portion 3b whose outer diameter decreases as it moves toward the front end (as it moves toward the cathode 4). A first coating 6 is formed on the cylindrical outer peripheral surface of the body portion 3a.

[0050] The melting point, vapor pressure, emissivity, and coefficient of thermal expansion of the first coating 6 become important. In order to reduce the temperature of the anode 3, the first coating 6 is preferably made of a material with high emissivity to increase heat dissipation.

[0051] The first coating 6 comprises a ceramic. The ceramic includes at least one of a metal oxide, a metal carbide, a metal boride, a metal silicide, and a metal nitride. The material of the first coating 6 can suitably be a material with a melting point above 2000°C, such as alumina (Al₂O₃), zirconium oxide (ZrO₂), zirconium carbide (ZrC), zirconium boride (ZrB₂), tantalum silicide (TaSi₂), and zirconium nitride (ZrN).

[0052] Figure 3 yes Figure 2 An enlarged sectional view of region III shown. (See attached image.) Figure 3 As shown, a concave-convex structure 30 is provided on the outer peripheral surface of the main body 3a of the anode 3. The concave-convex structure 30 is configured to have a plurality of circumferential grooves 31 arranged in the axial direction (X direction) extending in the circumferential direction of the main body 3a. Such circumferential grooves 31 can be formed, for example, by machining on a lathe. Furthermore, when forming the circumferential grooves 31 by machining on a lathe, multiple circumferential grooves 31 of one circumference can be arranged independently in the axial direction, or multiple circumferential grooves 31 can be arranged in a spiral continuous manner as a whole to form a spiral groove.

[0053] A first coating 6 is formed on the uneven surface of the uneven structure 30. The surface 6a of the first coating 6 has unevenness that reflects the uneven shape of the uneven structure 30. The unevenness that reflects the uneven shape of the uneven structure 30 improves heat dissipation.

[0054] The irregularities that appear on the surface 6a of the first coating 6 can be formed by controlling the thickness of the first coating 6. Figure 4 It is formed by comparison Figure 3 An enlarged cross-sectional view of the case with the thick first coating 6. (See image) Figure 4 As shown, when the thickness of the first coating 6 is thick, no unevenness reflecting the uneven shape of the uneven structure 30 is formed on the surface 6a, or even if it is formed, the unevenness is small.

[0055] Through dedicated research, the inventors discovered that in order to form a textured surface on the surface 6a of the first coating 6 that reflects the textured structure 30 formed on the surface of the anode 3, the thickness of the first coating 6 needs to be adjusted to satisfy the relationship 1 ≤ b / a ≤ 4, when the groove depth of the circumferential groove 31 is set to a (μm) and the distance from the bottom 311 of the circumferential groove 31 to the surface 6a of the first coating 6 is set to b (μm). Furthermore, the distance b can also be described as the thickness of the first coating 6 at the bottom 311 of the circumferential groove 31.

[0056] When b / a is less than 1, the thickness of the first coating 6 is too thin, and the peaks of the uneven structure 30 may be exposed. On the other hand, when b / a is greater than 4, the thickness of the first coating 6 is too thick, and the unevenness reflecting the uneven shape of the uneven structure 30 is not formed on the surface 6a of the first coating 6. Even if it is formed, the unevenness is small, and it is almost impossible to improve the heat dissipation effect.

[0057] The groove depth 'a' of the circumferential groove 31 is preferably 10 μm to 100 μm. When the groove depth 'a' is less than 10 μm, it is difficult to form unevenness on the surface 6a of the first coating 6. In addition, when the groove depth 'a' is greater than 100 μm, it is difficult to form the first coating 6 within the circumferential groove 31.

[0058] The height difference of the surface 6a is 5 μm or more, preferably 10 μm or more. When the height difference is less than 5 μm, it is difficult to achieve the effect of improving heat dissipation.

[0059] The thickness of the first coating 6 is preferably 10 μm or more. When the coating 6 is thin, sufficient emissivity cannot be obtained. In addition, in order to properly form unevenness on the surface 6a, the thickness of the first coating 6 is preferably 100 μm or less, more preferably 30 μm or less.

[0060] The formation of the first coating 6 is carried out, for example, by dispersing the particles of the material constituting the coating 6 (e.g., zirconium oxide particles with a particle size of less than 10 μm) into a solvent (e.g., a solvent composed of nitrocellulose and butyl acetate), applying it with a pen to the outer peripheral surface of the main body 3a of the anode 3, drying it at 150°C for 30 minutes, and then performing a heat treatment at 1900°C for 120 minutes in a vacuum atmosphere.

[0061] Figure 5 as well as Figure 6 This is an SEM image depicting a cross-section of the anode 3. Such a cross-sectional SEM image of the anode 3 can be obtained by first cutting the anode 3 with a grinder (blade), severing the anode 3 at the point of cutting, and then observing the fracture surface using a scanning electron microscope (SEM). The thickness of the first coating 6 can be determined using measurement software attached to the SEM.

[0062] Figure 5 The image is mapped when the groove depth a of the circumferential groove 31 is set to 30 μm and the distance b from the bottom 311 of the circumferential groove 31 to the surface 6a of the first coating film 6 is set to 50 μm, i.e., b / a is approximately 1.66. Figure 6 The image is mapped when the groove depth a of the circumferential groove 31 is set to 30 μm and the distance b from the bottom 311 of the circumferential groove 31 to the surface 6a of the first coating film 6 is set to 150 μm, i.e., b / a is 5. Figure 5 In the example shown, a textured surface 6a of the first coating 6 has a textured surface that reflects the textured structure 30. On the other hand, in Figure 6 In the example shown, the surface 6a of the first coating 6 has almost no unevenness reflecting the uneven shape of the uneven structure 30.

[0063] The front part 3b of the anode 3 can be shaped such that its outer diameter decreases as it faces the front end; it does not have to be like that. Figure 2 The shape shown is a conical trapezoid whose outer diameter decreases proportionally as it faces the front. For example, it could also be like... Figure 7 As shown, the outer peripheral surface of the electrode front portion 3b is configured such that the proportion of the outer diameter decreasing as it moves toward the front end changes, resulting in a curved cross-sectional shape.

[0064] Alternatively, on the surface of the front 3b of the electrode, such as Figure 8 As shown, a second coating 7 containing a metal with a higher melting point than ceramic is formed. The second coating 7, containing a metal with a higher melting point than ceramic, has higher heat resistance than ceramic, so it will not peel off when the lamp is lit. By providing this second coating 7, heat dissipation can be further improved.

[0065] Metals with a higher melting point than ceramics include, for example, tungsten. The second coating 7 is formed, for example, by dispersing tungsten particles in a solvent, applying them with a pen to the outer peripheral surface of the electrode front 3b of the anode 3, and then sintering.

[0066] Alternatively, a microgroove can be fabricated on the surface of the electrode front portion 3b without forming a second coating 7. By fabricating the microgroove, heat dissipation can be further improved. The microgroove fabrication can be performed using a laser processing machine. For example, the microgrooves can be formed with a depth of 650 μm and a spacing of 195 μm.

[0067] The embodiments of the present invention have been described above based on the accompanying drawings, but it should be considered that the specific structure is not limited to these embodiments. The scope of the present invention is not shown by the description of the above embodiments, but by the claims, and includes all modifications within the meaning and scope of the claims.

[0068] The structures used in the above embodiments can be applied to any other embodiments. The specific structures of each part are not limited to the above embodiments, and various modifications can be made without departing from the spirit of the invention. Furthermore, one or more of the structures, methods, etc. of the various modifications described below can be arbitrarily selected and used in the structures, methods, etc. of the above embodiments.

[0069] In the above embodiment, the first coating 6 is provided only on the outer peripheral surface of the anode 3. However, the first coating 6 can also be provided on the outer peripheral surface of the cathode 4, or the first coating 6 can be provided only on the outer peripheral surface of the cathode 4 without providing the first coating 6 on the outer peripheral surface of the anode 3.

[0070]

Example

[0071] Hereinafter, embodiments that specifically illustrate the structure and effects of the present invention will be described.

[0072] Multiple anodes 3 were fabricated with varying groove depth (a) of the circumferential groove 31 and thickness (b) of the first coating 6, as shown in Table 1. The circumferential groove 31 was formed by lathe machining. The groove depth of the circumferential groove 31 could be adjusted by changing the machining conditions of the lathe. The first coating 6 was formed as follows: Zirconia particles with a particle size of 10 μm or less were applied to a solvent composed of nitrocellulose and butyl acetate and well mixed, then applied to the outer circumferential surface of the anode 3 by pen. After drying at 150°C for 30 minutes, a heat treatment was performed at 1900°C for 120 minutes in a vacuum atmosphere. The thickness of the first coating 6 could be adjusted by changing the viscosity of the solvent used to disperse the zirconia particles.

[0073] The illuminance maintenance rate was evaluated after 500 hours of operation with a lamp equipped with a modified anode 3 at a rated power of 2kW (25V, 80A). Table 1 shows the evaluation results.

[0074] In addition, the illuminance maintenance rate was determined as follows: first, the illuminance at the start of illumination was measured using a photodetector sensitive to a wavelength of 365 nm; then, the illuminance was measured after 500 hours of continuous illumination at rated power, and the ratio to the initial illuminance was calculated.

[0075] In addition, the common specifications of all the lamps used in the test are as follows.

[0076] [Light-emitting diode]

[0077] Material: Quartz glass, Overall length: 70mm

[0078] Maximum diameter: φ55mm

[0079] Encapsulated substance: Mercury 2.5mg / cc

[0080] Electrode spacing: 5mm

[0081] [anode]

[0082] Material: Tungsten

[0083] Length: 30mm

[0084] Diameter of main body: φ20mm

[0085] [cathode]

[0086] Material: Thorium-coated tungsten

[0087] Length: 20mm

[0088] Diameter of main body: φ6mm

[0089] Table 1

[0090]

[0091] As shown in Table 1, when b / a is 0.8 and 5, regardless of the value of a, the illuminance maintenance rate after 500 hours of illumination is less than 80%. On the other hand, when b / a is 1 to 4, regardless of the value of a, the illuminance maintenance rate is over 80%.

[0092] Within the range of b / a from 1 to 4, anode 3 exhibits high heat dissipation, reducing the evaporation of electrode material and thus achieving a high illuminance maintenance rate. Furthermore, the effect is even greater (over 90%) within the range of b / a from 1 to 2.

[0093] Label Explanation

[0094] 1: Short-arc discharge lamp (lamp)

[0095] 2: LED

[0096] 3: Anode

[0097] 3a: Main body

[0098] 3b: Front part of electrode

[0099] 4: Cathode

[0100] 6: First Lamination

[0101] 6a: Surface of the first coating

[0102] 7: Second coating

[0103] 30: Concave-convex structure

[0104] 31: Zhou Xiang Cao

[0105] 311: Bottom of the circumferential groove

[0106] a: Groove depth of the circumferential groove

[0107] b: The distance from the bottom of the circumferential groove to the surface of the first coating.

Claims

1. A short-arc discharge lamp, wherein, The short-arc discharge lamp includes a light-emitting tube and a pair of electrodes disposed opposite to each other inside the light-emitting tube. At least one of the electrodes in the pair has a cylindrical outer peripheral surface. The outer peripheral surface has: an uneven structure with a plurality of circumferential grooves arranged axially and extending circumferentially; and a first coating comprising ceramic formed on the uneven surface of the uneven structure. When the groove depth of the circumferential groove is set to a (μm) and the distance from the bottom of the circumferential groove to the surface of the first coating is set to b (μm), the following relationship (1) is satisfied. The surface of the first coating has a height difference of more than 5 μm. 1≤b / a≤4 (1)。 2. The short-arc discharge lamp according to claim 1, wherein, The ceramic comprises at least one of metal oxides, metal carbides, metal borides, metal silicides, and metal nitrides.

3. The short-arc discharge lamp according to claim 1, wherein, The ceramic is mainly composed of zirconium oxide.

4. The short-arc discharge lamp according to claim 1, wherein, The electrode has an electrode front portion whose outer diameter decreases as it faces the front end. A second coating is formed on the surface of the front portion of the electrode, the second coating comprising a metal with a higher melting point than the ceramic.

5. The short-arc discharge lamp according to claim 1, wherein, The electrode has an electrode front portion whose outer diameter decreases as it faces the front end. Microgrooves are formed on the surface of the front part of the electrode.

Citation Information

Patent Citations

  • Discharge lamp and its electrode structure

    JP2004259639A

  • Method for roughening anode surface of short-arc high-pressure gas discharge lamp

    CN104018135A

  • Discharge lamp

    JP2017069078A

  • Short arc discharge lamp

    WO2021070459A1